Review of Recyclable Bio-based Epoxy Resins with Dynamic Chemical Bonds - Wan, Mengting; Liu, Xuemei; Zhang, Yuan (Journal of Chemical Engineering Research Updates, 2024)
Epoxy thermosetting resins are usually reliant on fossil fuel-based resources, commonly diglycidyl ether bisphenol A (DGEBA) type epoxy monomers. Most raw materials of these thermoset resin are toxic to the health of human, and their eternal cross-links make them difficult to reuse and recycle. To alleviate concerns about the environment and human health, it is an effective way to design new bio-based epoxy thermosetting materials to replace petroleum based thermosetting materials. The introduction of cleavable and dynamic bonds for bio-based thermosetting materials can also realize the recycling of bio-based epoxy resin. In this way, the damaged thermosetting materials can be recovered to prolong their service lifetime and reduce the thermosetting waste. This review article aims to outline the latest improvements in intrinsically recyclable bio-based epoxy thermosetting materials. This review first describes the synthesis method of recyclable bio-based epoxy, then reviews the structure, recyclable and other properties of bio-based epoxy containing different dynamic bonds, and finally summarizes the challenges and opportunities for the recyclable bio-based epoxy.